Mathematics Education in East Africa Towards Harmonization and Enhancement of Education Quality - Halai, Anjum; Tennant, Geoff (SpringerBriefs in Education, 2016)
*THIS BOOK WILL SOON BE AVAILABLE AS OPEN ACCESS BOOK* This book is a valuable resource for policymakers and practitioners as it brings insights mainly from developing countries where relatively less research activity takes place. It is also a valuable resource for courses in mathematics education in the teacher education colleges, and departments of education in the sub-Saharan Africa region. In the increasingly global and technological world mathematics is seen as a significant gatekeeper of opportunities for social and economic advancement and mobility. Hence, countries and development agencies in the broader sub-Saharan Africa region are looking towards increasing access to relevant and high-quality secondary education as a lever towards economic development. Policy makers and other key decision makers in education look towards improvement in mathematics teaching and learning as a key focus in education reform. In the East Africa region also a number of initiatives have been taken at the national level in the respective countries to improve the quality of mathematics education. This book provides an in-depth comparative analysis of the developments and issues in mathematics education in Kenya, Tanzania, Rwanda and Uganda, and advances our understanding of the state of secondary mathematics education in East Africa.